Modern Wound Treatment with Moist Wound Healing Effective for Healing Diabetic Ulcus - Ikrima Rahmasari; Fabiola Francisca Martins; Musta’an Musta’an; Iswanti Purwaningsih (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
Diabetes Mellitus is a metabolic disease that is chronic and requires ongoing medical care in a variety of ways that can reduce the risk of multi-factors beyond glycemic control. Uncontrolled diabetes mellitus will cause an increase in complications, one of which is diabetic ulcers. Achieving better wound healing is the main goal of diabetic ulcer management. Moisturizing dressings can provide a supportive environment for cells to carry out the wound healing process and prevent further damage or trauma. This study was to determine the effect of modern dressing with moist healing on diabetic ulcers. This type of research is a quantitative research with a quasi-experimental research design with an accidental sampling approach. Data was collected using demographic data and the Wocare For Indonesian Nurses (WINNERS) Scale assessment sheet which is a modified Bates-Jasen score to predict and evaluate the average score of wound healing. WINNERS scale consists of 10 assessments. The results of the intervention that have been carried out have shown a significant improvement in diabetic ulcers as assessed using the Bates Jensen Wound Assessment Tools. Based on the results and discussion, it was concluded that there was a significant effect of modern wound care using the moist wound healing method on the healing process of diabetic ulcers.